Effects of Oral Russian Hemp Seed Powder Supplementation on Reproductive Hormonal Profile and Selected Biochemical Traits in Ewes (Indian Journal of Animal Production and Management, 2026)
The study was conducted to determine the effect that oral feeding would  have on the Russian hemp seed powder on the ewes assessed based on  their measured hormonal, biochemical and protein related parameters. The  animals were randomly assigned and placed as three levels of experiment  where one of them was a control group )Without any additions( and two  levels of experimentation (where the animals were supposed to take the  Russian hemp seed powder (200 or 300 mg/ ewe /day) in capsules). In  the end of the experiment, blood samples were collected and serum of the  samples was assessed on estradiol, follicle-stimulating hormone (FSH),  anti-Mullerian hormone (AMH), cholesterol, glucose, urea and creatinine  and total protein and globulin. The processing of data was conducted in  a completely randomized study on XLSTAT 2016 and multiple range test  (Duncan), to determine significant differences in means in P = 0.05. Results  have indicated that oral administration of the Russian powder of the hemp  seed at different concentration rates had an enormous effect of amplifying  the serum estradiol and AMH specific concentration, that is, 300mg/ewe/ day, but not the FSH concentration. On the other hand, serum cholesterol,  glucose, urea levels were highly reduced in the treated groups than in the  control group yet creatinine was not. Treatment did not significantly differ  with a significant change in total protein and globulin. The correlation  analysis conducted on Pearson showed that estradiol is significantly  correlated with AMH and total protein and globulin between themselves.  The received findings allow concluding that oral nutritional supplement  of Russian hemp seed powder in a particular dose 300 mg/ewe/day can  potentially positively alter certain changes in reproductive hormones and  have a positive impact on certain biochemical parameters of ewes.
Keywords: Ewes, Russian hemp seed powder, Estradiol, Anti-Mullerian hormone, Biochemical characteristics.